TARIQ RAMADAN: INCLUSIVE AND PLURAL VALUE IN ISLAMIC INTELLECTUAL TRADITION - Ahmad Nabil Amir (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2022)
This paper aims to reflect the progressive ideal of reform of Tariq Said Ramadan (born 1962), an accomplished Muslim reformist dan leading exponent of modern Islam in 21th century and its instrumental impact based on his extensive philosophical writings. It argued that Ramadan was arguably the most influential modernist and its leading proponent in the modern history of Islam. The paper endeavors to analyze his modern ideal as articulated in his works such as What I Believe, Radical Reform, To Be A European Muslim and Western Muslims and the Future of Islam. Aspiring for meaningful realization of reform and inclusivism, it brought forth his perspective on minority Muslim in Europe and highlights its compelling and dynamic influence in modern intellectual discourse of civil Islam. Paul Donnelly in The Washington Post has rightly acclaimed him as “A Muslim Martin Luther”. His profound and discursive thoughts essentially emphasize on radical reform, pluralism and ijtihad (independent thinking), articulating its contextual interpretation and significant meaning. The study is based on qualitative method focusing on descriptive and historical analysis of related works and studies of his principal works. The finding shows that Ramadan has brought forth significant reform in the Muslim world that creatively responds to the present challenge of the western world. Tulisan ini bertujuan mengetengahkan pemikiran Tariq Said Ramadan (lahir 1962), reformis Islam abad ke dua puluh satu, dan menyorot pengaruh intelektual dan idea pembaharuan Islamnya dari sumber-sumber penulisannya yang ekstensif. Kajian membuktikan bahawa Ramadan merupakan antara penganjur Islam moden yang terpenting di abad ke-21. Idealisme pembaharuan ini diketengahkan dalam buku-bukunya seperti What I Believe, Radical Reform, To Be A European Muslim dan Western Muslims and the Future of Islam yang membawa filsafat pemikiran modennya dan tinjauannya tentang Islam dan masyarakat Muslim di Eropah. Pengembangan pengaruh intelektualnya di kalangan Muslim Eropah banyak terkesan oleh karya dan wacana modennya yang berpengaruh tentang semangat inklusivisme dan pluralisme, idea reform, masyarakat sivil, prinsip ijtihad dan pembelaan kaum minoriti. Paul Donnelly dalam The Washington Post mengungkapkannya sebagai “A Muslim Martin Luther” atau “Martin Luther-nya Islam”. Kaedah penelitian bersifat kualitatif, berasaskan tinjauan kepustakaan dan analisis kandungan terhadap sumber data secara deskriptif dan historis. Hasil kajian menyimpulkan bahawa Ramadan telah menggerakkan reformasi yang signifikan di dunia Islam dalam menghadapi tantangan moden Barat dan memainkan peran yang instrumental dalam membawa kesedaran budaya dan persefahaman nilai yang menentukan.